Antioxidant Activity of Pod Coat Extracts of Pigeon Pea (Cajanus Cajan L.) and Their Efficacy in Stabilization of Soybean Oil - Nehra Sukriti; Singh Sushila; Sangwan Seema; Rani Savita (Journal of Antioxidant Activity, 2021)
When lipids are exposed to heat, light and oxygen, it leads to oxidation. The addition of antioxidants is required to preserve colour, flavour and vitamin destruction. Present study was, therefore, planned to investigate pod coat of pigeon pea as possible sources of natural antioxidants and to assess their efficacy in stabilization of crude soybean oil during normal storage (28 days at 50°C). Study revealed that acetone pod coat extract of pigeon pea showed richness in total phenolics (17.72 mg/g), flavonoids (9.00 mg/g) and tannins (2.21 mg/g) while the extract of ethyl acetate was found enriched in tocopherols content (9.56 mg/g). The IC50 value of acetone extract was found to be lowest, exhibited potent antioxidant activity in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric thiocyanate (FTC) methods. After adding synthetic and natural antioxidants in oil, Peroxide, p-Anisidine, Thiobarbituric acid value, Conjugated dienes, trienes and free fatty acids content were measured every 4 days. Acetone pod coat extract (2000ppm) of pigeon pea gave strong antioxidant efficacy in stabilization of crude soybean oil and hence could be recommended as natural antioxidants for food applications.The research explored the possibility of using pod coat of pigeon pea as imminent sources of green antioxidants and to evaluate their efficacy in stabilization of crude soybean oil.
Keywords: Antioxidant